2021
DOI: 10.1021/acsnano.1c01250
|View full text |Cite
|
Sign up to set email alerts
|

Rich Heterointerfaces Enabling Rapid Polysulfides Conversion and Regulated Li2S Deposition for High-Performance Lithium–Sulfur Batteries

Abstract: The practical uses of lithium–sulfur batteries are greatly restricted by the sluggish reaction kinetics of lithium polysulfides (LiPSs), leading to low sulfur utilization and poor cyclic stability. Using the heterostructure catalysts is an effective way to solve the above problems, but how to further enhance the conversion efficiency and avoid the surface passivation by the insulative Li2S has not been well investigated. Herein, a heterostructure catalyst with rich heterointerfaces was prepared by modifying Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 46 publications
3
75
0
Order By: Relevance
“…It is noticed that S@Co/SA-Zn@N-C/CNTs electrode delivered a high initial capacity of 932 mAh g −1 and maintained a high capacity of 680 mAh g −1 after 800 cycles with a low capacity decay rate of 0.033% per cycle, which not only outperform those of S@Co@N-C/CNTs, S@SA-Zn@N-C, and S@N-C electrodes but also are superior to most developed TM/C/S cathodes (Figure 3e). [36][37][38][39][40][41][42][43][44][45][46][47] A large areal sulfur mass loading is crucial for the real application of Li-S batteries. We further investigated the cycle performance of S@Co/SA-Zn@N-C/CNTs cathode with increased sulfur loading.…”
Section: Resultsmentioning
confidence: 99%
“…It is noticed that S@Co/SA-Zn@N-C/CNTs electrode delivered a high initial capacity of 932 mAh g −1 and maintained a high capacity of 680 mAh g −1 after 800 cycles with a low capacity decay rate of 0.033% per cycle, which not only outperform those of S@Co@N-C/CNTs, S@SA-Zn@N-C, and S@N-C electrodes but also are superior to most developed TM/C/S cathodes (Figure 3e). [36][37][38][39][40][41][42][43][44][45][46][47] A large areal sulfur mass loading is crucial for the real application of Li-S batteries. We further investigated the cycle performance of S@Co/SA-Zn@N-C/CNTs cathode with increased sulfur loading.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the conductivity of CoNiO 2 and graphene, the polarization difference fully indicated that CoNiO 2 had a good catalytic function of polysulfides. [44] Meanwhile, the corresponding Tafel plots and slopes of all peaks were also calculated to quantify the catalytic activities (Figure 5b,c and Figure S11, Supporting Information). Evidently, the CoNiO 2 /Co 4 N-G-S electrode exhibited the lowest slopes at the oxidation of Li 2 S and the reduction of sulfur to long-chain sulfur species, implying the greatest improvement in the kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates the active sites of C@COF surface could guide the radical Li 2 S growth and the surface passivation can be avoided. [54,55] when using the CNTs, Li 2 S growth shows a tendency to 2DI model, which formed a uniform Li 2 S nucleation and made its surface easily passivated. [52] The Li 2 S dissolution kinetics was also evaluated.…”
Section: Characterizations Of C@cofmentioning
confidence: 99%